Tindak Pidana Kekerasan dalam Pacaran Serta Bentuk Pertanggungjawabanya - Siti Masyithah; Moh. R. U. Puluhulawa; Nuvazria Achir (Lembaga Pengembangan Kinerja Dosen, 2024)
The research results show that perpetrators of criminal acts of dating violence in the jurisdiction of the Gorontalo City Police are subject to criminal liability as regulated in Article 351 of the Criminal Code as simple assault or Article 466 of the Law of the Republic of Indonesia Number 1 of 2023 concerning the Code of Laws. Criminal law as the latest Criminal Code. So the perpetrator commits a violation of norms that is against the law. Factors that cause violence in dating in the Gorontalo City Police jurisdiction are: personality factors, violence in dating can be caused by the personality of the perpetrator himself; the factor of the victim being dependent on his partner, the victim being dependent on the perpetrator, the perpetrator naturally feels that whatever the perpetrator does will still be forgiven by the victim even if it is an act of violence; the influence of the family environment, when children witness aggression perpetrated by their parents, this can increase the likelihood of dating violence perpetrated by that individual; social influence, that being friends with friends who are often involved in violence can increase the risk of being involved in violence because there is the influence of social characteristics and motivation to commit violence itself; The influence of the place where violence occurs, the environment where violence occurs, which is mostly carried out in closed and quiet places, is a driving factor for this violence to continue to occur because the situation and conditions allow for violence to occur and the factor of gender inequality, violence in dating where the victims are more women, this is related to socio-cultural aspects that instill gender roles that differentiate men and women.